Menexenus - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1999)
"Menexenus" by Plato is a Socratic dialogue traditionally included in the seventh tetralogy. The work consists mainly of a funeral oration that Socrates claims to have learned from Aspasia, a prominent female Athenian philosopher. The speech praises Athens and recounts its military victories while parodying the style of traditional funeral oratory. Unique among Platonic dialogues, the actual conversation serves primarily as exposition for the lengthy oration itself. (This is an automatically generated summary.)
Socrates
Wikipedia page about this book: https://en.wikipedia.org/wiki/Menexenus_(dialogue)
Release date is 1999-03-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Rhetoric, Ancient; Rhetoric -- Philosophy